MGMT gene promoter methylation correlates with tolerance of temozolomide treatment in melanoma but not with clinical outcome - Hassel, Jessica C.; Sucker, Antje; Edler, Lutz; Kurzen, Hjalmar; Moll, I.; Stresemann, C.; Spieth, K.; Mauch, C.; Rass, K.; Dummer, R.; Schadendorf, Dirk (British journal of cancer, 2010)
Despite limited clinical efficacy, treatment with dacarbazine or temozolomide (TMZ) remains the standard therapy for metastatic melanoma. In glioblastoma, promoter methylation of the counteracting DNA repair enzyme O6-methylguanine-DNA-methyltransferase (MGMT) correlates with survival of patients exposed to TMZ in combination with radiotherapy. For melanoma, data are limited and controversial.